Exploring religious and/or spiritual identities: part 1 – assessing relationships with health. Issue 9 (21st October 2019) - Krause, Neal; Pargament, Kenneth I.; Hill, Peter C.; Ironson, Gail
ABSTRACT: There is considerable debate about the distinction between being religious and being spiritual. It is time to move beyond this issue to an examination of the health-related implications of being religious and/or spiritual. Three health outcomes are used in this study: self-rated health, depressive symptoms, and alcohol use. The data are from a large nationwide random probability survey of adults of all ages who reside in the United States ( N = 2, 876–2, 883). Four self-identified categories of religiousness/spirituality are examined: religious and spiritual, spiritual only, not religious/not spiritual, and religious only. Tests are performed to see if membership in each category offsets the noxious effects of lifetime trauma on the health-related outcomes. A clear pattern emerges from the data. Lifetime trauma is associated with less favourable health ratings, more symptoms of depression, and greater alcohol consumption. However, these relationships are substantially stronger among people who say they are religious only.